Muscle carnosine metabolism and [beta]-alanine supplementation in relation to exercise and training - Derave, W.; Everaert, I.; Beeckman, S.; Baguet, A. (Sports Medicine, 2010)
Carnosine is a dipeptide with a high concentration in mammalian skeletal muscle. It is synthesized by carnosine synthase from the amino acids L-histidine and ß-alanine, of which the latter is the rate-limiting precursor, and degraded by carnosinase. Recent studies have shown that the chronic oral ingestion of ß-alanine can substantially elevate (up to 80%) the carnosine content of human skeletal muscle. Interestingly, muscle carnosine loading leads to improved performance in high-intensity exercise in both untrained and trained individuals. Although carnosine is not involved in the classic adenosine triphosphate-generating metabolic pathways, this suggests an important role of the dipeptide in the homeostasis of contracting muscle cells, especially during high rates of anaerobic energy delivery. Carnosine may attenuate acidosis by acting as a pH buffer, but improved contractile performance may also be obtained by improved excitation-contraction coupling and defence against reactive oxygen species. High carnosine concentrations are found in individuals with a high proportion of fast-twitch fibres, because these fibres are enriched with the dipeptide. Muscle carnosine content is lower in women, declines with age and is probably lower in vegetarians, whose diets are deprived of ß-alanine. Sprint-trained athletes display markedly high muscular carnosine, but the acute effect of several weeks of training on muscle carnosine is limited. High carnosine levels in elite sprinters are therefore either an important genetically determined talent selection criterion or a result of slow adaptation to years of training. ß-Alanine is rapidly developing as a popular ergogenic nutritional supplement for athletes worldwide, and the currently available scientific literature suggests that its use is evidence based. However, many aspects of the supplement, such as the potential side effects and the mechanism of action, require additional and thorough investigation by the sports science community.